Mapping Yamunaji's linguistic landscape research: Cartographies in context, culture and class. Issue 1 (March 2015) - PANDEY, ANJALI; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT The current paper pays intellectual homage to a prolific scholar whose contributions to world Englishes need formal acknowledgement. Current linguistic landscape research it is argued stands to gain from Yamuna Kachru's timely theorizations. This paper situates Kachru's forty‐six year‐research within the chronoscope of her own evolving scholarly career to demonstrate the provocative implications of her brand of research. Her theorizations stand poised to re‐revolutionize the field's acknowledgement of linguistic rights particularly in regard to peripherally acknowledged, yet semiotically salient variables of pertinence to current research namely, context, culture and class which her research assiduously, indeed, meticulously sought to study.